Fuel Poverty Data Linking Project - Solomons, Craiger; Lowe, Sarah; Dixon, Josh; Whiffen, Tony; Bowen, Rachel; Davies, Matthew; Vine, Hugo (International Journal of Population Data Science, 2019)
Background with rationale In Wales, a household is considered to be in fuel poverty if it needs to spend more than 10% of its net income on maintaining a satisfactory heating regime. Addressing fuel poverty is particularly important to Wales with an estimated 29% of households in fuel poverty compared with 17% in the UK overall. To tackle fuel poverty in Wales, the Welsh Government implemented two fuel poverty schemes. Warm Homes Nest is a demand-led scheme and Warm Homes Arbed an area-based scheme. Both schemes provide free home energy efficiency measures e.g. home insulation or boilers. Main Aim To use linked administrative data to evaluate the impacts of Welsh Government home energy efficiency schemes for low income households. The findings will inform future fuel poverty schemes in Wales. Methods/Approach Individual-level data from both schemes was anonymously linked to routine health records, using the SAIL (Secure Anonymised Information Linkage) Databank, to examine the health service use of recipients. We used difference-in-difference estimations to compare any changes in the health of recipients before and after intervention with any concurrent change in health in those yet to receive an intervention. Results Results published in 2017 indicated positive effects for the Nest scheme, including positive impacts on respiratory health and general health. We will report results comparing the health impacts of the Arbed and Nest schemes. The study will be the first to directly compare the health impacts of a demand-led and an area-based energy efficiency scheme. Conclusion Providing home energy efficiency interventions has the potential to benefit population health; however, there is a scarcity of evidence comparing different methods of implementing schemes. Our findings will inform more effectively focussed home energy efficiency schemes and potentially improve the health of people living in Wales.